CREATION AND STEWARDSHIP: A CRITICAL ANALYSIS OF PATRISTIC THOUGHTS AND THEIR RELEVANCE IN THE CONTEMPORARY WORLD - Risu Na, Yaqin Wang, Ruo Jia, Buqi Na and Yucheng Ning (Journal of Dharma, 2024)
This study revisited the historical, scriptural, and theological foundations for the doctrine of creatio ex nihilo to re-establish the relevance of divine omnipotence, freedom, and creation in today’s world. A critico-religious approach has been employed for sharing biblical views in re-establishing philosophical conceptions to direct the world's understanding about 'creation out of nothing' and our stewardship. This piece argued that 'creation out of nothing' provides us the basis for understanding our religios and moral duty to this ecosystem. Therefore, on the one hand, rather than attacking worldly beliefs about creation, this paper has argued that emerging scientific and philosophical ideas about creation were not a threat throughout the defined patristic periods. Rather, the study has emerged as a result that has helped Christian thinkers in constructively reshaping such views. On the other hand, this paper has argued that in the past, the thoughts of the corporate world offered Christianity a unique opportunity to critically and constructively reflect on them to discover biblical truths. As a result, the approach toward this ethical shift aimed to build notions about the world's concepts of creation and our duty to be stewards on this earth.